Agricultural resilience in Central America: A key tool for prioritization and action against climate change - Gonzalez Rodriguez, Carlos Eduardo; Castillo Rivera, Johana Marcela; Eitzinger, Anton (2025)
To address climate change threats in Central America, CRS and the Alliance of Bioversity International and CIAT developed TOR2, a tool launched in 2024 to guide climate-resilient agriculture. TOR2 uses spatial data to assess the future suitability of 28 crops under different climate scenarios, helping prioritize actions across over 1,000 municipalities in the region. Built on earlier TORTILLAS projects, it supports decision-making for researchers, policymakers, and local actors. TOR2 is already aiding thousands of farmers and will expand under the CGIAR Policy Innovation program.